The Role of Macrophages in Oral Squamous Cell Carcinoma - Kalogirou, Eleni Marina; Tosios, Konstantinos I.; Christopoulos, Panagiotis F. (Frontiers in Oncology, 2021)
Oral cancer remains a common malignancy worldwide, with high disease-related death rates. Oral squamous cell carcinoma (OSCC) accounts for more than 90% of oral tumors, with surgical management remaining the treatment of choice. However, advanced and metastatic OSCC is still incurable. Thus, emphasis has been given lately in understanding the complex role of the oral tumor microenvironment (TME) in OSCC progression, in order to identify novel prognostic biomarkers and therapeutic targets. Tumor associated macrophages (TAMs) constitute a major population of the OSCC TME, with bipolar role in disease progression depending on their activation status (M1 vs. M2). Here, we provide an up to date review of the current literature on the role of macrophages during oral oncogenesis, as well as their prognostic significance in OSCC survival and response to standard treatment regimens. Finally, we discuss novel concepts regarding the potential use of macrophages as targets for OSCC immunotherapeutics and suggest future directions in the field.